Thrips and plant viruses: a comprehensive virome analysis in tropical agriculture - Zhang, Qikai; Cheng, Chunxi; Lyu, Baoqian; Gao, Yulin; Chen, Lilin; Peng, Liang; Yue, Zhengfu; Lu, Hui; Tang, Jihong; Jiao, Bin; Liu, Shen (Frontiers in Microbiology, 2025)
IntroductionThrips are key vectors for plant viruses, representing a significant challenge to the cultivation of cucurbits and other vegetables in tropical agriculture. This study investigates the diversity of viromes carried by thrips and their ecological roles in viral epidemics affecting specific crops.MethodsWe identify thrips populations in tropical regions and perform a comprehensive virome analysis through high-throughput sequencing.ResultsOur findings reveal that the predominant thrips species associated with these crops are Frankliniella intonsa, Thrips palmi, and Megalurothrips usitatus. The sequencing efforts identified 19 viruses within these thrips, including previously undocumented viruses, such as a double-stranded RNA virus and several positive- and negative-sense single-stranded RNA viruses. Notably, detection rates of specific plant viruses—Melon yellow spot virus (MYSV), Watermelon silver mottle virus (WSMoV), and Telosma mosaic virus (TeMV)—exhibit significant correlations with thrips population density in cucurbits and other vegetables.DiscussionThis study lays the groundwork for future research into the ecological relationships between thrips and plant viruses, offering valuable insights for developing targeted disease management strategies in tropical agricultural systems.